Holmium: YAG Versus Cold Knife Internal Urethrotomy in the Management of Short Urethral Strictures: A Randomized Controlled Trial: Holmium Versus Cold Knife VIU - Gamal, Mohamed A.; Higazy, Ahmed; Ebskharoun, Samuel F.; Radwan, Ahmed (Journal of Lasers in Medical Sciences, 2021)
Introduction: our study aimed to assess the safety and efficacy of Holmium: YAG laser internal urethrotomy compared to the cold knife internal urethrotomy. Methods: Eighty adult male patients presented with a urethral stricture less than 1.5 cm were included in our study; they were randomly allocated into 2 groups representing Holmium and cold knife internal urethrotomy. A careful evaluation with ascending cystourethrogram and uroflowmetry were done on all patients, and they were followed up for 1 year with uroflowmetry. Results: Each group included 40 patients sharing the same demographic data. The most common cause of a urethral stricture in both groups was iatrogenic injury. The mean operative time of the cold knife urethrotomy procedure was 10.98 ± 2.40 minutes compared to 15.43 ± 2.48 minutes in the holmium laser urethrotomy group with a highly significant difference. The results showed success rates of 90% and 80% for the holmium laser and cold knife internal urethrotomy groups respectively. The perioperative complication according to the Clavien-Dindo classification, showed no statistically significant difference in grade 1 and 2 complications. A recurrence rate with the need for redo surgery representing grade 3B complication was seen in 4 cases in the Holmium group compared to 8 cases in the cold knife group with a statistically significant difference. Conclusion: Both Holmium Laser and cold knife internal urethrotomy are effective surgical options for the treatment of a urethral stricture less than 1.5 cm with a promising outcome after 1-year follow-up with a better success rate using the Holmium laser. Doi:10.34172/jlms.2021.35